Twice-Daily Theta Burst Stimulation of the Dorsolateral Prefrontal Cortex Reduces Methamphetamine Craving: A Pilot Study - Zhao, Di; Li, Yongqiang; Liu, Ting; Voon, Valerie; Yuan, Ti-Fei (Frontiers in Neuroscience, 2020)
Objectives: Theta burst stimulation (TBS) has been recently shown to be non-inferior relative to repetitive transcranial magnetic stimulation for major depression. Here we aim to assess the tolerability and clinical efficacy of intermittent or continuous accelerated theta burst stimulation (iTBS/cTBS) for drug craving. The study compare the clinical efficacy and tolerability of intermittent and continuous theta burst stimulation protocols targeting left or right dorsolateral prefrontal cortex on methamphetamine craving in abstinent dependent subjects. Methods: In this randomized single-blind pilot study, 83 abstinent methamphetamine dependent subjects from a long-term residential treatment program were randomly allocated into three groups: iTBS over the left DLPFC (active group), cTBS over the left DLPFC (active control group) or cTBS over the right DLPFC (active group) was administered twice-daily over five days for a total of 10 sessions. We measured the primary outcome of cue-induced craving and secondarily sleep quality, depression, anxiety, impulsivity scores and adverse effects. Results: We show a pre- versus post-intervention effect on craving which on post-hoc paired t-tests analysis showed the effect was driven by iTBS of the left DLPFC and cTBS of the right DLPFC reducing cue induced craving but not cTBS of the left DLPFC. We did not show the critical Group by Time interaction. The secondary outcomes of depression, anxiety and sleep were unrelated to the improvement in craving in the left iTBS and right cTBS group. In the first two sessions, self-reported adverse effects were higher with left iTBS when compared to right cTBS. The distribution of craving change suggested greater clinical response (50% improvement) with right cTBS and a bimodal pattern of effect with left iTBS suggesting high inter-individual variable response in the latter. Conclusion: Accelerated twice-daily TBS appears feasible and tolerable at modulating craving and mood changes in abstinent methamphetamine dependence critically while reducing session length. We emphasize the need for a larger randomized controlled trial study with a sham control to confirm these findings and longer duration of clinically relevant follow up.